Charting the early history of Penang trading networks and its connections with the new ASEAN growth triangle (Malaysia- Indonesia-Thailand) - Nordin Hussin, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2007)
This paper charts the early history of Penang trading networks and its connections with northern Indonesia and southern Thailand .The discussion points out that the current IMT (Indonesia- Malaysia-Thailand)growth triangle is not a new phenomenon for this region and for Penang in particular. For much of the eighteenth century, Penang’s identity and commercial viability were seen to depend on its role as a hub for surrounding sub-regional economies. The main inter-state corridor had a long history as a route of trade and suppression that placed Penang’s fortunes in ever closer proximity to those of Southern Siam, Kedah, Perak, Aceh, Burma and the Coromandel Coast of India. The discussion further illustrates the importance of Penang as the main source of accumulated capital and Chinese labour which played different roles in the process of mining development. Finally, a point is made about the importance of Penang as a key contributor towards the acceleration of the economic growth and social transformation of southern Thailand, as well as for the northern region of Sumatra